The Production Of Bluder Substitute Made Of Psyllium Husk Flour As Fiber-Rich Food To Prevent Constipation - Warsito, Heri; Choiri, Haniva Imanda; Iqbal, Muhammad; Putra, Dony Setiawan Hendyca (P3M Politeknik Negeri Jember, 2025)
Continuous constipation can cause several diseases such as hemorrhoids, colon cancer, diverticular disease. It is generally characterized by stool which becomes increasingly harder and larger. As a result, this causes lower frequency of defecation. Consuming highly fibrous food sources is one decent measure to address constipation. One ingredient high in fiber is psyllium husk. This study aims to determine the fiber content in bluder made of psyllium husk flour as a bread substitute to prevent constipation. It employed Completely Randomized Design (CRD) with 5 treatments (flour and psyllium husk flour), inter alia T1 (87.6% and 12.4%), T2 (86.4% and 13.6%), T3 (85.2% and 14.2%), T4 (84% and 16%), and T5 (82.2% and 17.2% flour), each of which was repeated 5 times. The results showed that T5 has the highest fiber content at 9.85 grams/60 grams. The addition of psyllium husk flour had a significant effect on fiber content and the physical properties of bluder, while the best treatment in this study was T3 (85.2% flour and 14.8% psyllium husk flour). One loaf of bluder weighing 65 grams provides energy content of 228 kcal, 9 grams of protein, 8 grams of fat, 30 grams of carbohydrates, and 4.8 grams of fiber.